Serological response following re-vaccination with Salmonella typhi Vi-capsular polysaccharide vaccines in healthy adult travellers. Issue 33 (7th August 2015) - Roggelin, Louise; Vinnemeier, Christof D.; Fischer-Herr, Johanna; Johnson-Weaver, Brandi T.; Rolling, Thierry; Burchard, Gerd D.; Staats, Herman F.; Cramer, Jakob P.
Abstract: An injectable Vi-capsular polysaccharide vaccine against typhoid fever is available but vaccine-induced immunity tends to wane over time. The phenomenon of immunotolerance or hyporesponsiveness has earlier been described for polysaccharide vaccines such as pneumococcal capsular polysaccharide vaccine and some publications also suggest a possible immunotolerance after revaccination with Vi-capsular polysaccharide vaccines. In this study, post-immunisation antibody concentrations in adult travellers first vaccinated with a Salmonella typhi Vi-capsular polysaccharide vaccine (primary vaccination group) were compared with those having received one or more vaccinations previously (multiple vaccinations group). Vaccines administered were Typherix ® (GlaxoSmithKline), Typhim Vi ® (Sanofi Pasteur MSD) or Hepatyrix ® (GlaxoSmithKline). Blood samples were obtained prior to vaccination (day 0) and on day 28 (−1/+14) after vaccination. Serum Vi-Antigen IgG concentrations were measured by ELISA. Of the 85 subjects included in the per protocol data set, 45 (53%) belonged to the multiple vaccinations group. In both groups, geometric mean antibody concentrations (GMCs) were significantly higher after vaccination than before vaccination. Pre-vaccination GMCs were lower in the primary vaccination group than in the multiple vaccinations group (3.40 μg/ml versus 6.13 μg/ml, P = 0.005), while there was no significant difference in the post vaccination GMCs between groups (11.34 μg/ml versus 14.58 μg/ml, P = 0.4). In the multiple vaccinations group, vaccination was performed 18 to 57 months after the last vaccination (median 38 months) and there was a negative correlation between time since last vaccination and antibody concentration on day 0. In conclusion, we were not able to demonstrate a relevant immunotolerance after multiple versus primary vaccination with S. typhi Vi-capsular polysaccharide vaccines.